Structure-reactivity analysis of novel hypervalent iodine reagents in S-vinylation of thiols - Doobary, Sayad; Di Tommaso, Ester Maria; Postole, Alexandru; Inge, A. Ken; Olofsson, Berit (Frontiers in Chemistry, 2024)
The transition-metal free S-vinylation of thiophenols by vinylbenziodoxolones (VBX) constituted an important step forward in hypervalent iodine-mediated vinylations, highlighting the difference to vinyliodonium salts and that the reaction outcome was influenced by the substitution pattern of the benziodoxolone core. In this study, we report several new classes of hypervalent iodine vinylation reagents; vinylbenziodazolones, vinylbenziodoxolonimine and vinyliodoxathiole dioxides. Their synthesis, structural and electronic properties are described and correlated to the S-vinylation outcome, shedding light on some interesting facets of these reagents.